Strain rate sensitivity of the tensile strength of two silicon carbides: experimental evidence and micromechanical modelling. (28th January 2017) - Zinszner, Jean-Luc; Erzar, Benjamin; Forquin, Pascal
Abstract : Ceramic materials are commonly used to design multi-layer armour systems thanks to their favourable physical and mechanical properties. However, during an impact event, fragmentation of the ceramic plate inevitably occurs due to its inherent brittleness under tensile loading. Consequently, an accurate model of the fragmentation process is necessary in order to achieve an optimum design for a desired armour configuration. In this work, shockless spalling tests have been performed on two silicon carbide grades at strain rates ranging from 10 3 to 10 4 s −1 using a high-pulsed power generator. These spalling tests characterize the tensile strength strain rate sensitivity of each ceramic grade. The microstructural properties of the ceramics appear to play an important role on the strain rate sensitivity and on the dynamic tensile strength. Moreover, this experimental configuration allows for recovering damaged, but unbroken specimens, giving unique insight on the fragmentation process initiated in the ceramics. All the collected data have been compared with corresponding results of numerical simulations performed using the Denoual–Forquin–Hild anisotropic damage model. Good agreement is observed between numerical simulations and experimental data in terms of free surface velocity, size and location of the damaged zones along with crack density in these damaged zones. This article is part of the themed issue 'Experimental testing and modelling of brittle materials at high strain rates'.